Detector Development for a Double-Differential Cross Section Experiment with the Emission of Light Charged Particles from High Energy Neutrons - Dietz M.; Beyer R.; Junghans A.; Nolte R.; Pirovano E.; Romanets Y.; Vaz P. (EPJ Web of Conferences, 2023)
Double-differential cross section (DDX) data on the neutron-induced emission of light charged particles are required for assessing the risk of secondary tumors in particle radiation therapy. There are only very few DDX data available for discrete neutron energies close to and above 100 MeV for carbon. A measurement of DDX on carbon is planned at continuous neutron energies from 20 MeV to 200 MeV with particle detector telescopes at n_TOF (CERN). Several detector development criteria and challenges are reported such as coincidence timing and electromagnetic oscillations for high neutron energy events with particle separation.